Digitalisasi Pendidikan Karakter: Mengoptimalkan Peran Pembelajaran Akidah Islam Sebagai Perisai di Era Digital di MTs Sunan Giri Maron - Lya Ayu Firnanda; Herwati; Yeniati Ulfah (Irfani, 2026)
This study aims to describe the role of Islamic Creed (Akidah Islam) learning in strengthening students’ character education in the digital era at MTs Sunan Giri Maron. This research employed a qualitative approach with a field research design. Data collection techniques were conducted through observation, interviews, and documentation to obtain in-depth and accurate data. The research informants included the headmaster, Akidah Akhlak teachers, and students who were directly involved in the learning process. The results of the study indicate that Islamic Creed learning plays a very important role in shaping students’ religious and moral character as a shield against the negative influences of digital technology development. In addition, the use of digital media such as smartphones, laptops, and projectors helps make the learning process more effective, interesting, and easier for students to understand. Supporting factors in character building come from the support of the madrasah, teachers, parents, and the surrounding community environment. This study concludes that Islamic Creed learning not only focuses on cognitive aspects but also plays an important role in shaping students’ attitudes, behavior, and religious character in the digital era